(untitled) (Indian Journal of Arid Horticulture, 2016)
An experiment was conducted during 2010-11 and 2011-12 in poly-house at Niche Area Excellence Farm, Bikaner to study the effect of drip irrigation and fertigation levels on plant height, fruit yield, and water use efficiency of capsicum. The treatments consists of three drip irrigation schedules viz. 40, 60 and 80% ETc and three fertigation levels viz. 75%, 100% and 125% of recommended dose of fertilizers. The experiment was conducted in randomized block design and replicated thrice. The study indicated that there was increase in plant height, fruits /plant and fruit yield with increase in irrigation levels from 40% to 80% ETc. but the water use efficiency decreases with increasing irrigation levels. The study further indicated that plant height, fruits /plant, fruit yield and water use efficiency also increased with increasing the fertigation levels from 75% to 125% recommended dose of fertilizer.